Socialization of Learning Computer Technology for ANBK Exam Preparation at SDN 2 Pandeyan, Ngemplak District, Boyolali Regency : Socialization of Learning Computer Technology for ANBK Exam Preparation at SDN 2 Pandeyan, Ngemplak District, Boyolali Regency - Rifai, Dian Muhammad; Nathaniel, Kenny; Rohman, Jundur; Alim, Generusatindo Alim; Yusup, Arfan (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2023)
Abstract:With the rapid development of information and communication technology, the learning of science must be given from an early age, especially in the field of education at the elementary level. We are trying to improve the science and technology with the intention of preparing for the upcoming ANBK exam. The Community Service entitled Socialization of Computer Technology Learning for ANBK Exam Preparation at SDN 2 Pandeyan, Ngemplak District, Boyolali Regency was carried out on Tuesday 1 August 2023 to Wednesday 2 August 2023. The aim is to provide science and technology knowledge and skills to students at SDN 2 Pandeyan who Never operated on a computer. The method used is socialization and direct practice of computer operation and ANBK exam simulation. The result of this activity is that Pandeyan 2 Elementary School students have skills in operating computers both for daily needs and for ANBK exams. Keywords: ANBK, Computer, and SD